Correlation between Degree of Gibbus Angulation, Neurological Deficits, and Pain in Spondylitis Tuberculosis Patients - Rizkiditia Nugraha Hadian; Renaldi Prasetia; Ahmad Faried (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To analyze the correlation between the degree of angulation and neurological deficits as well as pain in spondylitis tuberculosis (TB) patients.Methods: This observational-analytic study included bivariate analysis on data collected from the medical records of patients with presented with spondylitis TB to Dr. Hasan Sadikin General Hospital, Bandung outpatient clinic from January 2014 to December 2015. The variables were the degree of gibbus angulation, neurological deficits, and pain.Results: The study showed significant positive correlation between gibbus angulation and sensory neurological deficits (r=0.375; p=0.009) and there was significant positive correlation between gibbus angulation and pain (r=0.638, p=0.000). The study showed an insignificant correlation between gibbus angulation and motoric neurological deficits (r=0.125; p=0.525).Conclusions: There is a significant correlation between the degree of gibbus angulation and pain as well as sensory neurological deficits. Meanwhile, no significant correlation is found between the degree of gibbus angulation and motoric neurological deficits.Keywords: Gibbus angulation, neurological deficits, pain, spondylitis tuberculosis DOI: 10.15850/ijihs.v5n2.1049